Development of the GeoGebra’s Guidebook in Creating Mathematics Learning Media Based on Ethnomathematics - Lekitoo, John Nandito; Kurniati MA, Ratnah; Sugiarto, Sigit; Dahoklory, Andy Sunder Keer; Inuhan, Michael; Rupilele, Karolina (Universitas Ahmad Dahlan, 2024)
This research aims to develop a guidebook for the use of GeoGebra in creating mathematics learning media based on ethnomathematics for university students in mathematics education study program at Pattimura University PSDKU Maluku Barat Daya. The method used in this research is Research and Development (R&D) with 4D model developed by Thiagarajan et al. (1974) which consists of 4 stages, namely Define, Design, Develop and Disseminate. This method and model are very feasible and systematically supports the development of the guidebook. By involving 2 validators, namely material experts and linguists, the draft of the guidebook was then revised and tested on a small limited group. Furthermore, based on descriptive statistical analysis and qualitative descriptive analysis, it can be concluded that the reference book using GeoGebra has been successfully prepared and meets the criteria of valid and effective. In addition, the use of this guidebook can also increase students' knowledge in understanding material related to cartesian coordinates, especially in drawing graphs of linear functions, quadratic functions, polynomials, trigonometric functions, exponent functions, and logarithms.